PILOTING A NEW SET OF THE AEER ACCREDITATION CRITERIA - Sergei I. Gerasimov; Sergei B. Mogilnitskiy; Alexander I. Chuchalin; Polina S. Shamritskaya; Sergei O. Shaposhnikov (Высшее образование в России)
The article presents a new set of the accreditation criteria for engineering and technology educational programs approved and implemented by the Association for Engineering Education of Russia (AEER) since 2014. The criteria were developed in accordance with Russian professional standards, Federal State Educational Standards, as well as international standards such as EUR-ACE Framework Standards and Guidelines and IEA Graduate Attributes and Professional Competencies. In 2014-2015 the AEER accreditation criteria were piloted by the accreditation of engineering technicians and master degree programs offered by Russian universities and technical schools / colleges. The results of the criteria piloting are described and analyzed. The objectives for the development of Russian national accreditation system for educational programs in engineering and technology are defined, which include integration in internationally recognized structures such as European Network for Accreditation of Engineering Education (ENAEE) and International Engineering Alliance (IEA).